Is 'summer' reading loss universal? Using ongoing literacy assessment in Malawi to estimate the loss from grade-transition breaks. (December 2017) - Slade, Timothy S; Piper, Benjamin; Kaunda, Zikani; King, Simon; Ibrahim, Hibatalla
Summer learning loss – decreased academic performance following an extended school break, typically during the period after one grade ends and before another grade starts – is a well-documented phenomenon in North America, but poorly described in sub-Saharan African contexts. In this article, we use the term 'grade-transition break' loss in lieu of 'summer' loss to refer to the period after one grade ends and before another grade starts. This study analyses data from early grade reading assessments in Malawi, estimating statistically significant average reductions of 0.38 standard deviations (SD) across several measures of reading and pre-reading skills during two grade-transition breaks. The data show the loss in reading skills during the extended breaks between grades 1 and 2 and between grades 2 and 3 in two consecutive years. The study found no gender-based differences in loss. The findings suggest a need for early grade reading interventions to develop and evaluate mitigation strategies lest significant proportions of within-year performance gains be lost over the break between academic years.